2015
DOI: 10.1021/acs.orglett.5b01616
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-Catalyzed Intramolecular Aminodifluoromethylation of Unactivated Alkenes

Abstract: A photoredox catalyzed aminodifluoromethylation of unactivated alkenes has been developed in which HCF2SO2Cl is used as the HCF2 radical source. Sulfonamides were active nucleophiles in the final step of a tandem addition/oxidation/cyclization process to form pyrrolidines, and esters were found to cyclize to form lactones. Thus, a variety of pyrrolidines and lactones were obtained in moderate to excellent yield. In order for the cyclization reactions to be efficient, a combination of a copper catalyst (Cu(dap)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…of NaHCO 3 as a base to neutralize the equivalent of HCl generated during the reaction based on our initial hypothesis, and we were encouraged to observe a significant increase in product yield (up to 91%) and with good enantioselectivity (82% ee) and found that no hydroamination byproduct was observed (entry 2). A thorough evaluation of different inorganic salts indicated that they have significant impact on the efficiency and enantioselectivity; and Ag 2 CO 3 was found to be particularly effective (entries 2–7)37. Noteworthy is that Ag 2 CO 3 was used to improve the product yield of the intramolecular aminofluoroalkylation reaction in racemic form under photoredox catalysis37.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…of NaHCO 3 as a base to neutralize the equivalent of HCl generated during the reaction based on our initial hypothesis, and we were encouraged to observe a significant increase in product yield (up to 91%) and with good enantioselectivity (82% ee) and found that no hydroamination byproduct was observed (entry 2). A thorough evaluation of different inorganic salts indicated that they have significant impact on the efficiency and enantioselectivity; and Ag 2 CO 3 was found to be particularly effective (entries 2–7)37. Noteworthy is that Ag 2 CO 3 was used to improve the product yield of the intramolecular aminofluoroalkylation reaction in racemic form under photoredox catalysis37.…”
Section: Resultsmentioning
confidence: 99%
“…A thorough evaluation of different inorganic salts indicated that they have significant impact on the efficiency and enantioselectivity; and Ag 2 CO 3 was found to be particularly effective (entries 2–7)37. Noteworthy is that Ag 2 CO 3 was used to improve the product yield of the intramolecular aminofluoroalkylation reaction in racemic form under photoredox catalysis37. Its good performance compared with other inorganic bases might be due to the generation of the highly insoluble AgCl and weaker carbonic acid to ensure unselective background reactivity is minimal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction involves a C-N bond forming step which is the result of the interaction of the unsaturated C=C bond and the difluoromethyl radical generated from HCF 2 SO 2 Cl by copper based Cu(dap) 2 Cl photocatalyst and visible light (Figure 10). 41 Alkenes (26), having tosylated terminal amino-function are converted into 2-difluoroethyl-pyrrolidines (28), except those bearing better nucleophiles, such as carboxylate-substituents which afforded the corresponding lactones.…”
Section: C-heteroatom Bond Formation: N O S P-functionalizationmentioning
confidence: 99%